Characterization of Asbestos in Ambient Air During Refractory Material Production From Magnesite Ore - Küçüker, Mehmet Ali; Küçüker, Mehmet Ali (Çanakkale Onsekiz Mart Üniversitesi, 2021)
Asbestos is a general term employed for crystallized silicate minerals in fibril form. It can be commonly found in nature and from which fibre uses in the industry through processing are obtained. It is dielectric and fibrous, having an elastic feature. However, there is limited information about the air quality in terms of asbestos for the companies that produce refractory materials from magnesite ore. This deficiency in the literature can be eliminated with this study for a company with high quality and durable refractory materials. Among the most commonly used asbestos analysis are scanning electron microscope (SEM), transmission electron microscope (TEM). Asbestos analyses have been performed in two different institutions on the parallel samples whose preliminary processes have been completed. According to the results of the examinations conducted by SEM, 23 of the fibrils observed in a total area are bigger than five µmin lengths and less than 3 µm in width. Three of these fibrils were observed to have the characteristics of chrysotile fibres morphemically and elementally. In addition, airborne samples were analyzed using a TEM instrument. According to the results obtained, 13 of the fibrils observed in total were bigger than 5 µm in length and less than 3 µm in width and based on ED analysis and elemental composition (EDXA) results of these fibrils, and they were not observed to have the characteristics of chrysotile fibres. The majority of the fibrils observed were noted to be other inorganic minerals (lizardite) fibrils. Additionally, the obtained results show that the asbestos concentration in the air is below the limit specified by the provision (0,1 fiber/cm3).
Keywords: Asbestos; Ambient air; Magnesite ore; Asbestos exposure; Morphologic analysis